Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1088/1361-6463/aaa285
|View full text |Cite
|
Sign up to set email alerts
|

Collimated dual species oven source and its characterisation via spatially resolved fluorescence spectroscopy

Abstract: We describe the design, construction and characterisation of a collimated, dual-species oven source for generating intense beams of lithium and caesium in UHV environments. Our design produces full beam overlap for the two species. Using an aligned microtube array the FWHM of the output beam is restricted to ∼ 75 milliradians, with an estimated axial brightness of 3.6×10 14 atoms s −1 sr −1 for Li and 7.4×10 15 atoms s −1 sr −1 for Cs. We measure the properties of the output beam using a spatially-resolved flu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…For instance, in a dual Li/Cs beam, the Li behavior was the brightwall one where the Cs flux was found to be a factor 130 times smaller than expected in Ref. 35 [an alternative explanation for this discrepancy (involving worse light-gathering because of Cs coating the windows) is given in the article, but we believe it is instead just another observation that indeed Cs ovens almost always exhibit dark-wall behavior]. It was also clearly observed that following the oven installation and pumping, it takes time (hours for an oven at >120 ○ C or days if lower temperature) to see any Cs flux out of the tube.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…For instance, in a dual Li/Cs beam, the Li behavior was the brightwall one where the Cs flux was found to be a factor 130 times smaller than expected in Ref. 35 [an alternative explanation for this discrepancy (involving worse light-gathering because of Cs coating the windows) is given in the article, but we believe it is instead just another observation that indeed Cs ovens almost always exhibit dark-wall behavior]. It was also clearly observed that following the oven installation and pumping, it takes time (hours for an oven at >120 ○ C or days if lower temperature) to see any Cs flux out of the tube.…”
Section: Discussionmentioning
confidence: 60%
“…or physical variables (temperature, pressure, etc.). 34 However, discrepancies between the calculated flux and measured flux of cesium ovens, common in the literature, 35 indicate that other factors can be preponderant. Indeed, the usual flux calculations consider no chemical interaction between emitted atoms and the surface of the tube.…”
Section: Introductionmentioning
confidence: 99%